Summary of the 5th Global Science Conference on Climate-Smart Agriculture - Dinesh, Dhanush (2019)
The 5th Global Science Conference on Climate-Smart Agriculture brought together over 410 participants, from more than 200 institutions, based in over 60 countries. This included participants from research institutions, governments, private sector and civil society, to catalyze action oriented partnerships for a transformation in our food systems, under a changing climate. Detailed summaries of thematic discussions are captured in this document.